2015
DOI: 10.4149/bll_2015_119
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of nano-zinc oxide

Abstract: INTRODUCTION: Nowadays, a lot of studies were carried out about side effects of nanoparticles especially nano-zinc oxide, but unfortunately, most of these studies have been conducted with high doses. MATERIAL AND METHODS: In the present study 36 male Wistar rats with approximate age of two months and weighing 300 ± 30 g were selected. After standard phases of preparation, injections were done intraperitoneally in chronic groups with zinc oxide nanoparticles (20 and 40 mg/kg) every other day and for acute group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The dose level of ZnONPs (10 μg/kg per week, i.v., 4 weeks) was determined based on pilot trials, as there was no previous study performed on ZnONPs in vivo regarding anticancer potential. This dose level was much lower than the dose levels applied in acute or chronic studies for ZnONPs in rodents …”
Section: Methodsmentioning
confidence: 85%
“…The dose level of ZnONPs (10 μg/kg per week, i.v., 4 weeks) was determined based on pilot trials, as there was no previous study performed on ZnONPs in vivo regarding anticancer potential. This dose level was much lower than the dose levels applied in acute or chronic studies for ZnONPs in rodents …”
Section: Methodsmentioning
confidence: 85%
“…The marked decrease in lymph%, WBC, and MCHC may result from the blood leakage from the vessel walls caused by high doses of ZnO-NPs [37]. Espanani et al [38] reported similar hematological results for acute ZnO-NPs administration. However, Ben-Slama et al [31] results are inconsistent with ours; they found no hematological changes after ZnO-NPs ingestion.…”
Section: Discussionmentioning
confidence: 86%
“…According toLiu et al (2015) zinc oxide nanoparticles can lead to increase in white and RBC, a decrease in lymphocyte count, and an increase in neutrophil count. By utilizing the same doses and routes administration of ZnO NPs but with various administration times up to 21 days,Espanani et al (2015) demonstrated in this period a decrease in the counts of platelet and lymphocyte with an increase in white cell count and no effect on the red cell count. Depending on the administered dose, sub-chronic use of zinc oxide…”
mentioning
confidence: 82%